Curative and eradicant action of fungicides to control Phakopsora pachyrhizi in soybean plants - Reis,Erlei Melo (2016)
ABSTRACT Experiments were carried out in a growth chamber and laboratory to quantify the curative and eradicant actions of fungicides in Asian soybean rust control. The experiments were conducted with the CD 214 RR cultivar, assessing the following fungicides, separately or in association, chlorothalonil, flutriafol, cyproconazole + trifloxystrobin, epoxiconazole + pyraclostrobin, cyproconazole + azoxystrobin, and cyproconazole + picoxystrobin. The fungicides were applied at four (curative) and nine days after inoculation (eradicant treatment). Treatments were evaluated according to the density of lesions and uredia/cm2, and the eradicant treatment was assessed based on the necrosis of lesions/uredia and on uredospore viability. Except for the fungicide chlorothalonil, there was curative action of latent/virtual infections by the fungicides. Penetrant fungicides that are absorbed have curative and eradicant action to soybean rust.